A Novel investigation of building integrated photovoltaic thermal (BiPVT) system: A comparative study. (June 2016) - Rajoria, C.S.; Agrawal, Sanjay; Chandra, Subhash; Tiwari, G.N.; Chauhan, D.S.
Highlights: Comparative analysis of BiPVT. Analysis by the thermal load leveling. Higher Qun of semitransparent PVT roof. Abstract: In this paper, the expressions of room air temperature for building integrated photovoltaic thermal (BiPVT) system installed at the roof of a building have been obtained and at the same time performance evaluation of BiPVT has been investigated. A comparative analysis of Building integrated photovoltaic thermal system based on the arrays described namely (i) solar cell tile (SCT) array and (ii) semi-transparent PVT array has been carried out. In the earlier study; the performance analysis and comparison has been done for opaque and semi-transparent BiPVT systems with a single flow configuration (non-optimized), whereas in this study the evaluation has been done on optimized duct. It is important to note that the analysis of BiPVT roof with SCT array has been performed for the first ever time. It has been observed that the useful thermal energy gain for semi-transparent PVT roof is significantly higher than SCT roof. The highest useful thermal energy gain for semi-transparent PVT roof is higher by 2.0 kW h which reflects its higher heat removal characteristics. Further, an attempt has been made to analyze the thermal load leveling (TLL) with respect to number of air changes ( No ) for both the systems. It has been observed here; that the thermal load leveling for both the systems breaks even at number of air changes less than four which implies that, for both the systems, thermal comfort is achieved when the number of air changes is less than four. Therefore, it can be well assumed that the optimum TLL may be achieved when it is lying between 3 and 4 number of air changes.